2016
DOI: 10.1371/journal.pone.0168954
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Weakened Intercellular Coupling in the Mammalian Circadian Clock under Long Photoperiod

Abstract: For animals living in temperate latitudes, seasonal changes in day length are an important cue for adaptations of their physiology and behavior to the altered environmental conditions. The suprachiasmatic nucleus (SCN) is known as the central circadian clock in mammals, but may also play an important role in adaptations to different photoperiods. The SCN receives direct light input from the retina and is able to encode day-length by approximating the waveform of the electrical activity rhythm to the duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(104 citation statements)
references
References 42 publications
11
92
1
Order By: Relevance
“…It will be intriguing to map the synaptic network topology that contributes to the phase relationships among SCN cells (Abel et al, 2016;Buijink et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It will be intriguing to map the synaptic network topology that contributes to the phase relationships among SCN cells (Abel et al, 2016;Buijink et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…16.039.001) was granted by the animal experiments committee Leiden. The homozygous PERIOD2::LUCIFERASE (PER2::LUC) mice were bred at the Leiden University Medical Center animal facility (see Buijink et al, 2016). We used young (4-8 months) and old (22-28 months) male PER2::LUC mice.…”
Section: Animals and Housingmentioning
confidence: 99%
“…Therefore, we measured PER2::LUC expression in SCN cultured slices of old and young mice after the mice were reexposed for at least 2 weeks to either LP or SP following the DD period. We have previously shown that exposing young mice to LP (LD 16:8) causes a wider phase distribution of peak times and a higher cycle-to-cycle period variability of single-cell PER2::LUC rhythms in the anterior part of the SCN compared with SP (LD 8:16; Buijink et al, 2016). Since we see deficits in behavioral adaptation to photoperiod in old mice, and photoperiod can affect PER2 rhythm distribution, we may expect that the reduction in the capability to adapt to photoperiod is also seen at the molecular level.…”
Section: Response Of the Molecular Clock Network To Photoperiod Is Unmentioning
confidence: 99%
“…The electrical activity patterns of single SCN neurons are less affected by photoperiod (VanderLeest et al., ) and the single‐cell waveform changes reported are not sufficient to explain adaptation of the ensemble output to day‐length (Brown & Piggins, ). Similarly studies of clock gene expression show a change in the distribution of peak expression in response to different photoperiods (Buijink et al., ; Naito, Watanabe, Tei, Yoshimura, & Ebihara, ), but also reveal spatial differences between dorsal and ventral (Evans, Leise, Castanon‐Cervantes, & Davidson, ), and between caudal and rostral SCN (Hazlerigg, Ebling, & Johnston, ; Inagaki, Honma, Ono, Tanahashi, & Honma, ). Thus, while the rhythm generating properties arise in individual cells, seasonal encoding depends on the integrity and plasticity of the SCN network.…”
Section: Neuronal Synchronization: Measuring Daylength and Coping Witmentioning
confidence: 82%